Still around the issue of writing in higher education: teaching and research demands - Assis, Juliana Alves; Bailly, Sophie; Corrêa, Manoel Luiz Gonçalves (Scripta, 2017)
In this text, we aim to address topics related to the project sponsored by Capes-Cofecub called “Discurso acadêmico na pesquisa e no ensino: questões em torno da apropriação da palavra de outrem” (Academic discourse in research and teaching: about appropriating other’s words) (N. 834/15), which is also featured in the organization of this edition of the journal Scripta.